PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN KOMUNIKASI MELALUI DISIPLIN KERJA TERHADAP PENINGKATAN KINERJA GURU DI SMPN 7 BALIKPAPAN - Yuni Astuti; Nugroho Mardi Wibowo; Woro Utari (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This research is to know the description of participative leadership style, communication, work discipline and teacher performance at SMPN 7 Balikpapan. In detail this research is to know the influence of participative leadership style and communication on teacher performance, influence of participative leadership style and communication to work discipline, influence of work discipline and participative leadership style on teacher performance at SMPN 7 Balikpapan through work discipline; as well as to know the communication on teacher performance at SMPN 7 Balikpapan through work discipline. This research uses quantitative approach and explanatory research type. Methods of data collection using questionnaires and documentation. The population in this study were all teachers at SMPN 7 Balikpapan. The sample of this study amounted to 47 teachers. The sampling technique uses a saturated sample. The results of this study indicate the style of participative leadership and communication in persial significant effect on the discipline of teachers at SMPN 7 Balikpapan. Communication and work discipline have a significant effect on teacher performance at SMPN 7 Balikpapan. Participatory leadership style has a significant effect on teacher performance at SMPN 7 Balikpapan through work discipline. Communication has a significant effect on teacher performance in SMPN 7 Balikpapan through work discipline. Keywords: participative leadership style, communication, work discipline, and teacher performance